Jumlah eosinofil darah tepi dan mukosa hidung pad penderita Rhinitis Alergika di RS Dr Muwardi Surakarta - Ermawati, Dwi Arini; Candrawati, Susiana (Jurnal Keperawatan Soedirman, 2008)
Eosinophile is an alergic indicator especially in rhinitis alergic disease found increase an eosinophile on either capillary blood or nasal mucosa dominantly. The aim of this research was to know the correlation of the capillary blood and nasal mucosa eosinophil amount. The reseach conducted in Muwardi hospital, Surakarta with 70 samples that consist of 40 rhinitis allergica and 30 controls. The data analyzed by chi square test and correlation by Pearson product moment. The result of this research showed there was an eosinophil amount difference between samples and controls significantly (p < 0,05). The amount of eosinophile on capillary blood positive correlated with nasal mucosa significantly (p< 0,05). The conclusion of this research was the increasing amount of eosinophile on capillary blood followed by increasing on nasal mucosa.Ã‚Â Ã‚Â